Hydrocracking of Non-edible Vegetable Oils with Co-Ni/HZSM-5 Catalyst to Gasoil Containing Aromatics - Danawati Hari Prajitno; Achmad Roesyadi; Muhammad Al-Muttaqii; Lenny Marlinda (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
Biofuel has been considered as one of the environmentally friendly energy sources to substitute fossil fuel derived from non-edible vegetable oil. This research aims to investigate the effect of the non-edible vegetable oil composition on a specific hydrocarbons distribution contained in biofuel and the aromatics formation through hydrocracking reaction with the Co-Ni/HZSM-5 catalyst. The formation of aromatics from non-edible vegetable oils, such as: Cerbera manghas, rubber seed, and sunan candlenut oils, containing saturated, mono- and polyunsaturated fatty acids is presented. The hydrocracking reaction was carried out in a pressure batch reactor, a reaction temperature of 350 oC for 2 h, reactor pressure of 15 bar after flowing H2 for 1 hour, and a catalyst/oil ratio of 1 g/200 mL. Liquid hydrocarbon product was analyzed by gas chromatography-mass spectrometry. Based on the GC-MS analysis, hydrocracking on three different oils indicated that polyunsaturated fatty acids were required to produce relatively high aromatics content. The sunan candlenut oil can be converted to gasoil range hydrocarbons containing a small amount of aromatic through hydrocracking reaction. Meanwhile, the aromatics in liquid product from hydrocracking of Cerbera manghas and rubber seed oils were not found.